2023
DOI: 10.3389/fphys.2023.1122504
|View full text |Cite
|
Sign up to set email alerts
|

Effects of wetted inner clothing on thermal strain in young and older males while wearing ventilation garments

Abstract: The present study examined the effect of wearing a water-soaked inner t-shirt with a ventilation garment on thermal and cardiovascular strain in eight young (26 ± 4 years) and eight older (67 ± 3 years) men undertaking moderate-intensity work (metabolic rate: 200–230 W m−2) in a hot environment (37°C, 50% RH, 2.8 kPa). While intermittent walking in hot conditions for 60 min, as a control (CON), the subject wore a dry inner t-shirt (long-sleeved) without fanning of a ventilation jacket (single-layered cotton, 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…The effects of wetted inner clothing on thermal strain in young and older males were investigated using a wear trial test when wearing a ventilative jacket. The results showed that wearing a water-soaked inner T-shirt while using a ventilation jacket reduced thermal and cardiovascular strains in young and old individuals working under hot conditions 15 . In another study, sports t-shirts made from cotton and polyester were used in a wear trial, and the skin temperature, heart rate, body sweat loss and sweat absorption of garments were investigated.…”
Section: Introductionmentioning
confidence: 98%
“…The effects of wetted inner clothing on thermal strain in young and older males were investigated using a wear trial test when wearing a ventilative jacket. The results showed that wearing a water-soaked inner T-shirt while using a ventilation jacket reduced thermal and cardiovascular strains in young and old individuals working under hot conditions 15 . In another study, sports t-shirts made from cotton and polyester were used in a wear trial, and the skin temperature, heart rate, body sweat loss and sweat absorption of garments were investigated.…”
Section: Introductionmentioning
confidence: 98%